2015
DOI: 10.12957/demetra.2015.15116
|View full text |Cite
|
Sign up to set email alerts
|

Correspondência Entre a Percepção Materna E O Estado Nutricional De Escolares

Abstract: Correspondência entre a percepção materna e o estado nutricional de escolares Correspondence between maternal perception and students' nutritional status Resumo Introdução: A percepção materna do estado nutricional do filho (PM), quando discordante do estado nutricional diagnosticado (EN), pode propiciar distúrbios nutricionais. Objetivo: Avaliar a correspondência entre a PM e o EN de escolares, bem como os fatores associados. Métodos: Amostra de 518 escolares de 7 a 10 anos. Foram coletados dados antropométri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1
4

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 21 publications
0
4
1
4
Order By: Relevance
“…A high percentage of mothers underestimated the nutritional status of their overweight children (39,3%), a trend that has been previously observed among parents of this population [8,7,12,13,14,31,32]. However, contrary to previous findings, 29.9% of mothers of overweight children and 47.9% of those of obese children overestimated the nutritional status of their child.…”
Section: Discussioncontrasting
confidence: 83%
See 4 more Smart Citations
“…A high percentage of mothers underestimated the nutritional status of their overweight children (39,3%), a trend that has been previously observed among parents of this population [8,7,12,13,14,31,32]. However, contrary to previous findings, 29.9% of mothers of overweight children and 47.9% of those of obese children overestimated the nutritional status of their child.…”
Section: Discussioncontrasting
confidence: 83%
“…With regard to child's sex, it could be seen that boys were more likely to have their nutritional status underestimated by their mothers, whereas girls were more likely to have it overestimated. Other studies also found an association between child's sex and maternal perception of nutritional status [ 12 , 28 , 32 , 34 ]. Mothers tend to be more concerned about the nutritional status of their daughters, wishing them to be thinner.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations